C-phycocyanins: Immune system modulation and its possible application as therapy against cancer - Alfaro-Alfaro, Álvaro Esteban (2020)
Cancer is a complex, heterogeneous, and dynamic disease, characterized by uncontrolled mitosis. Historically, it has been treated with surgery, radiotherapy and chemotherapy, and in more recent years through immunotherapy. For this, different proteins have been investigated for the modulation of the immune response. A group of these are C-phycocyanins, biliproteins from bluish-green microalgae such as Spirulina platensis. The anti-inflammatory environment in healthy people is a prophylactic measure to reduce the risk of developing a certain type of cancer. Its intake has shown that behavior, by suppressing the release of pro-inflammatory substances. An immunomodulatory effect has also been appreciated by increasing or decreasing the expression of CD59, as well as by causing the macrophage proliferation and the release of inflammatory substances. The latter is an indication that there is insufficient information to corroborate its use as a prophylactic or therapeutic option against cancer. Therefore, the information about natural substances such as this one is transcendental, because although they are more attractive to treat this disease, there are no fully proven therapeutic effects.